Case Studies on Effective Strategies for Measuring and Evaluating Social Outcomes and Societal Contributions in Nonprofit Organizations - Khare, Parth (Journal of Advanced Research in Nonprofit Organizational Governance and Social Impact Measurement; Vol 1 No 1 (2025): Journal of Advanced Research in Nonprofit Organizational Governance and Social Impact Measurement, 2025)
Nonprofit organizations play a critical role in addressing social, educational, environmental, and health-related issues globally. However, for these organizations to maintain accountability and maximize their social impact, it is essential to have robust mechanisms for measuring and evaluating their outcomes. This article presents case studies from various nonprofit organizations, focusing on effective strategies used to assess their social outcomes and societal contributions. The study highlights both successes and challenges, providing insights into best practices, methodologies, and tools that can be employed by nonprofits to evaluate their programs effectively.